2018
DOI: 10.1177/1934578x1801300831
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Insecticidal Properties of Juniperus thurifera Leaves

Abstract: The hydro-distilled essential oil from the leaves of Juniperus thurifera L. (JTEO) was analyzed by GC-MS and examined for its insecticidal, antifungal and antioxidant activities. A total of 51 compounds were identified. The major components were sabinene (22.4%), followed by terpinen-4-ol (11.0%) and α-pinene (5.9%). JTEO exhibited interesting insecticidal activity against adults of Acanthoscelides obtectus, Tribolium castaneum and Sitophilus oryzae, with LC 50 values of 0.1, 0.6 and 2.0×10-2 µL/mL, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Many strategies had been devoted to the control of A. flavus, F. oxysporum, A. niger, and C. albicans using different types of substances, either natural or chemically synthesized. Our results are in agreement with previous reports e.g., the study of Jemli et al [51], which showed a substantial antifungal activity against A. alternata, F. solani, F. oxysporum, V. dahlia, and R. solani with a percentage of inhibition ranging from 24% to 92.1%.…”
Section: Negative Control Foxysporum Calbicanssupporting
confidence: 94%
“…Many strategies had been devoted to the control of A. flavus, F. oxysporum, A. niger, and C. albicans using different types of substances, either natural or chemically synthesized. Our results are in agreement with previous reports e.g., the study of Jemli et al [51], which showed a substantial antifungal activity against A. alternata, F. solani, F. oxysporum, V. dahlia, and R. solani with a percentage of inhibition ranging from 24% to 92.1%.…”
Section: Negative Control Foxysporum Calbicanssupporting
confidence: 94%
“…However, regarding the control of Verticillium wilts in general and VWO in particular, only a few studies are available. For instance, the hydro-distilled essential oil from the leaves of Juniperus thurifera L. was able to inhibit the mycelial growth of different phytopathogenic fungi, including V. dahliae [192]. Similarly, the variable in vitro mycelial growth inhibition of S. sclerotiorum, F. oxysporum, and V. dahliae was observed with essential oils extracted from Vaccinium myrtillus L., Laurus nobilis L., and Eucalyptus camaldulensis Dehnh [193,194].…”
Section: Plant Extracts Essential Oils and Seaweedsmentioning
confidence: 99%
“…The ferric reducing antioxidant power assay was performed according to a previously established protocol [9]. Various concentrations of MEMC (0.25-1 mg/mL) were adjusted to a 2.5 mL volume and combined with 2.5 mL 0.2 M phosphate buffer (pH 6.6), and 2.5 mL 1% aqueous potassium hexacyanoferrate [K 3 Fe(CN) 6 ] solution.…”
Section: In Vitro Antioxidant Effectmentioning
confidence: 99%